2014
DOI: 10.1016/j.meegid.2014.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology, phylogeny and evolution of the filarial nematode Wuchereria bancrofti

Abstract: Wuchereria bancrofti (Wb) is the most widely distributed of the three nematodes known to cause lymphatic filariasis (LF), the other two being Brugia malayi and B. timori. Current tools available to monitor LF are limited to diagnostic tests targeting DNA repeats, filarial antigens, and anti-filarial antibodies. While these tools are useful for detection and surveillance, elimination programs have yet to take full advantage of molecular typing for inferring infection history, strain fingerprinting, and evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 81 publications
1
21
0
Order By: Relevance
“…Genetic structure is the result of movement of parasites within, but not between, transmission zones: parasites within a transmission zone interbreed and are genetically more similar to each other than to parasites in another transmission zone, with whom they do not interbreed. The likelihood that parasites are from the same transmission zone, and thus likelihood of parasite transmission between two locations (invasion), can therefore be inferred from the degree of genetic relatedness between them (e.g., Blouin et al, 1995;Nadler, 1995;Criscione and Blouin, 2004;Small et al, 2014). Statistically significant genetic differentiation at neutral loci (i.e., loci which do not affect a phenotype subject to selection pressure) between two parasite samples indicates that they originate from two separate transmission zones ( Figure 4).…”
Section: Conceptual Approachmentioning
confidence: 99%
“…Genetic structure is the result of movement of parasites within, but not between, transmission zones: parasites within a transmission zone interbreed and are genetically more similar to each other than to parasites in another transmission zone, with whom they do not interbreed. The likelihood that parasites are from the same transmission zone, and thus likelihood of parasite transmission between two locations (invasion), can therefore be inferred from the degree of genetic relatedness between them (e.g., Blouin et al, 1995;Nadler, 1995;Criscione and Blouin, 2004;Small et al, 2014). Statistically significant genetic differentiation at neutral loci (i.e., loci which do not affect a phenotype subject to selection pressure) between two parasite samples indicates that they originate from two separate transmission zones ( Figure 4).…”
Section: Conceptual Approachmentioning
confidence: 99%
“…Previous researches have shown that evolutionary features offer fresh views to many important fields that are related to drug discovery, including immunology [ 6 ], physiology [ 7 , 8 ], epidemiology [ 9 ] and neurosciences [ 10 ]. Wang et al [ 11 ] conducted an analysis and showed that some targeted genes shared common evolutionary features, which suggested that evolutionary information might provide novel insights for characterizing drug targets from new perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Ten PacBio SMRT cells were run for an estimated coverage of 20-40X. Whole genomes were aligned using progressiveCactus (https://github.com/glennhickey/progressiveCactus) with a guide tree reconstructed from whole mitochondrial genomes [Small et al, 2014]. Ragout [Kolmogorov et al, 2014] was run allowing for repeat resolution with scaffolds named according to B. malayi reference genome.…”
Section: Improvement Of the Wb Draft Genome Sequence And Gene Annotationmentioning
confidence: 99%